Indifferent, skeptical, ambivalent, moderate, and enthusiastic: What impacts profiles of teachers' technology views - Jaehong Jang; Hawon Yoo; Ksan Rubadeau (Social Sciences and Humanities Open)
Teachers' views about information and communication technology are a key affordance or barrier to classroom technology adoption and use. However, in determining factors that impact these views, much research has relied on variable-centered approaches that bifurcated teachers' views into mere positive or negative groups. Such approaches oversimplify key information that could serve educational authorities attempting to address low technology integration in schools. Therefore, this large-scale study employed a latent profile analysis with multilevel logistic regression analysis that aimed to (1) identify profiles of teachers' views of information and communication technologies for teaching and learning and (2) explore effects from teacher- and school-level variables on these profiles. Utilizing nationally generalizable data from 2079 full-time eighth-grade teachers from 150 different schools across South Korea from the International Computer and Information literacy study 2018, the analysis revealed five profiles of teachers' views: Indifferent, Skeptical, Ambivalent, Moderate, and Enthusiastic, with Moderate being the largest, and Highly Ambivalent and Indifferent the smallest. The findings from multilevel logistic regression analysis indicated numerous effects from teacher- and school-level antecedents and processes that matched each profile, highlighting school leaders’ ICT views. Notably, there were no effects from regional differences. Implications for leaders and policymakers are discussed in the context of professional development and reform policies.